1980
DOI: 10.1111/j.1528-1157.1980.tb04318.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Disorders Following Periodic Lateralized Epileptiform Discharges

Abstract: We reviewed 3,436 EEGs and found 24 patients with periodic lateralized epileptiform discharges (PLEDS). The etiology was unknown in 7, cerebrovascular occlusion in 7, tumor in 3, intracerebral hematoma in 2, and subdural hematoma, neonatal asphyxia, electrolyte imbalance, subarachnoid hemorrhage, and hypoglycemia in each of the remaining cases. We were successful in contacting 18 patients and/or their families for follow-up. Twenty of the 24 patients with PLEDS had seizures. Seven had focal motor alone, 10 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
2
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 8 publications
(11 reference statements)
3
39
2
1
Order By: Relevance
“…Most surprisingly, we found a highly significant association between the occurrence of PLEDs before NCS and prolonged NCS series. This is in agreement with previous findings of an association between severe seizure activity and PLEDs (34,37,38,53,57). For instance, Snodgrass et al (41) found that over 50% of all patients they catalogued with PLEDs exhibited electrographic status epilepticus.…”
Section: Periodic Lateralized Epileptiform Dischargessupporting
confidence: 82%
See 1 more Smart Citation
“…Most surprisingly, we found a highly significant association between the occurrence of PLEDs before NCS and prolonged NCS series. This is in agreement with previous findings of an association between severe seizure activity and PLEDs (34,37,38,53,57). For instance, Snodgrass et al (41) found that over 50% of all patients they catalogued with PLEDs exhibited electrographic status epilepticus.…”
Section: Periodic Lateralized Epileptiform Dischargessupporting
confidence: 82%
“…The normally functioning brain is solely dependent upon induced, including traumatic brain injury, hemorrhage, or blood-delivered glucose as an energy source for the stroke [15,29,37]. Anticonvulsant therapy with agents production of adenosine-triphosphate (ATP).…”
Section: Reportable Outcomes For Year'03mentioning
confidence: 99%
“…The importance of EEG timing in the detection of epileptiform abnormalities has not been generally appreciated, despite the fact that at least one study has clearly demonstrated that the incidence of periodic EEG patterns increases when they are performed earlier in the course of the disease process 8,9 .…”
mentioning
confidence: 99%
“…Among the clinical manifestations, seizures are the most important and striking feature associated with PLEDs, occurring with a frequency from 58 to 100% 2,[8][9][10][11] . This wide range probably reflects the heterogeneity of patient selection and study design.…”
mentioning
confidence: 99%
See 1 more Smart Citation